English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2. 3m-2/ 2m(squared) - 5m -3 - 2/ 2m+1 = 4/ m-3

3. Find a quadratic equation of the form ax(squared) + bx +c =0

a. 3/2 , -4
b. 3 + radical 5 , 3 - radical 5

2007-01-02 17:45:55 · 4 answers · asked by cfishot 2 in Science & Mathematics Mathematics

i need help!

2007-01-02 18:27:35 · update #1

4 answers

(3m - 2)/(2m^2 - 5m -3) - 2/(2m+1) = 4/(m-3)
(3m - 2) = 4(2m + 1) + 2(m - 3)
3m - 2 = 8m + 4 + m - 6
6m = 0
m = 0

-2/-3 - 2 =? 4/-3
-2 = 6/-3

3.
a.
(x - 3/2)(x + 4) = 0
(2x - 3)(x + 4) = 0
a = 2
b = 5
c = - 12

b.
(x - 3 - √5)(x - 3 + √5) = 0
x^2 - 3x + x√5 -3x + 9 -3√5 -x√5 + 3√5 - 5 = 0
x^2 - 3x -3x + 9 - 5 = 0
a = 1
b = - 6
c = 4

2007-01-02 20:25:00 · answer #1 · answered by Helmut 7 · 0 0

wats the a and b for??

3m-2/ 2m^2- 5m -3 - 2/ 2m+1 = 4/ m-3

wait this question isn't clear: - 5m -3 - 2/ 2m+1 are there supposed to be brackets newhere?

2007-01-03 02:43:17 · answer #2 · answered by turtles 3 · 0 0

2) 3m-2/ 2m² - 5m -3 - 2/ 2m+1 = 4/ m-3
3m-2 over (2m+1)(m-3) minus 2 over 2m+1 = 4 over m-3
LCF(2m²-5m-3; 2m+1; m-3)= (2m+1)(m - 3)
3m - 2 - 2(m-3) = 4(2m + 1)
3m - 2 - 2m + 6 = 8m + 4
3m - 2m - 8m = 4 -6 + 2
-7m = 0
m = 0
<>

2007-01-03 09:56:08 · answer #3 · answered by aeiou 7 · 0 0

Hey, these aren't fun. These are busywork.

2007-01-03 01:53:56 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers